2022
DOI: 10.3897/subtbiol.73.79318
|View full text |Cite
|
Sign up to set email alerts
|

Divergent evolutionary pathways for aggression and territoriality in Astyanax cavefish

Abstract: The surface morph of the Mexican tetra fish (Astyanax mexicanus) exhibits strong territoriality behavior and high levels of aggression. In contrast, the eyeless cave-adapted morph from Sierra de El Abra, México, rarely are aggressive and have totally lost the territorial behavior. These behaviors are part of what has been called the cavefish behavioral syndrome. Here, we report that several Astyanax cave populations of Sierra de Guatemala, unlike those reported for the Sierra de El Abra cave populations, displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Interestingly, when quantifying hair cell afferent neurotransmission across other cavefish populations, the authors found that Molino cavefish displayed an intermediate phenotype (Lunsford et al., 2022 ). This fits well with previous findings addressing other questions in A. mexicanus , where Molino cavefish have displayed intermediate phenotypes within physiological and behavioral contexts (Espinasa et al., 2022 ; Riddle et al., 2018 ; Rodriguez‐Morales et al., 2022 ; Xiong et al., 2018 ), and is another instance where ecological, cave‐specific contributions might be underlying cave‐trait variation.…”
Section: Sensitivity Of the Cavefish Lateral Linesupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, when quantifying hair cell afferent neurotransmission across other cavefish populations, the authors found that Molino cavefish displayed an intermediate phenotype (Lunsford et al., 2022 ). This fits well with previous findings addressing other questions in A. mexicanus , where Molino cavefish have displayed intermediate phenotypes within physiological and behavioral contexts (Espinasa et al., 2022 ; Riddle et al., 2018 ; Rodriguez‐Morales et al., 2022 ; Xiong et al., 2018 ), and is another instance where ecological, cave‐specific contributions might be underlying cave‐trait variation.…”
Section: Sensitivity Of the Cavefish Lateral Linesupporting
confidence: 90%
“…Another behavior that evolved reductions in blind cavefish populations of the Mexican tetra is aggression (Parzefall & Hausberg, 2001). Previous work from others and I showed that multiple populations of A. mexicanus cavefish exhibit reductions in aggressive behaviors (Elipot et al, 2013;Espinasa et al, 2022;Rodriguez-Morales et al, 2022). Although one might think that not seeing another individual would eliminate social interactions, in A. mexicanus, surface fish remain aggressive when visually deprived, while blind Molino cavefish conserved aggressive behaviors (Rodriguez-Morales et al, 2022).…”
Section: Social Behaviors: Schooling and Aggressionmentioning
confidence: 99%
“…At the phenotypic level, the partial complementation restoring sight in blind cavefish larvae after crosses between different cave populations [ 15 ], the loss of schooling behaviour that is very similar between Pachón and Tinaja but shows some differences in Molino [ 41 ], or the complete loss of aggressiveness in Sierra de El Abra populations but less so in Sierra de Guatemala populations [ 42 , 43 ] are also in favour of a common origin followed by independent evolution. Likewise, the observation that, among genes whose rhythmic expression is lost in at least one of three caves, 22% were arrhythmic in the three caves, was interpreted as evidence of repeated evolution of circadian clock dysregulation in independent populations [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the phenotypic level, the partial complementation restoring sight in blind cavefish larvae after crosses between different cave populations [13], the loss of schooling behaviour that is very similar between Pachón and Tinaja but shows some differences in Molino [38], or the complete loss of aggressiveness in Sierra de El Abra populations but less so in Sierra de Guatemala populations [39,40] are also in favour of a common origin followed by independent evolution. Likewise, the observation that, among genes whose rhythmic expression is lost in at least one of three caves, 22% were arrhythmic in the three caves, was interpreted as evidence of repeated evolution of circadian clock dysregulation in independent populations [41].…”
Section: Remarkable Convergence or Common Origin Of Cave Traits?mentioning
confidence: 99%